Drug delivery systems for oral cancer treatment: A patent perspective - Mohamed Hassan Dehghan; Abrar Abdul Malik Siddiqui (Oral Oncology Reports)
Oral cancer is a highly prevalent disease affecting millions worldwide. Major risk factors for oral cancer include tobacco and alcohol use, HPV infections, poor nutrition, and genetic susceptibility. The disease progresses through multiple genetic and epigenetic alterations involving tumor suppressors like p53, p16, and FHIT, along with oncogenes like EGFR, c-yc, K-ras, int-2, PRAD-1, and bcl leading to the development of premalignant lesions and subsequent tumors. Surgery, radiation, and chemotherapy are conventional therapies used against oral cancer, though they have numerous side effects. This necessitates the development of alternative therapeutic strategies like targeted drugs, immunotherapies, photodynamic therapy, and delivery systems based on nanotechnology. The paper provides an extensive review of patents pertaining to novel therapeutics, formulations, and treatment methods for oral cancer. Patents encompass siRNA, antibodies, immune checkpoint inhibitors, antimicrobial peptides, natural products like curcumin, nanoparticle drug carriers, and bioadhesive electrospun fibers loaded with drugs. Major routes of administration covered are oral, parenteral, mucoadhesive patch, rectal, topical, etc. Common excipients used are PEG, PLGA, lipids, surfactants, preservatives, salts, permeation enhancers, etc. The review study shows assays like RT-PCR, immunohistochemistry, animal carcinoma models, and cytotoxicity tests to demonstrate anticancer efficacy. The review insights into emerging oral cancer therapies and facilitates further research in this area.